Reconstruction of tourism infrastructure in de occupied territories - Medvid, Anna (Запоріжжя: ТДАТУ, 2026)
War damages the infrastructure of roadways, housing, cultural institutions and leisure spaces, especially within Zaporizhzhia and along the Azov Sea shorelines. The tourism industry, once a major contributor to economic development and jobs, is experiencing significant drops in both due to ongoing threats to security and damage sustained to supporting infrastructure. Restoration of tourism will be a key force in revitalising economies, reconstructing communities and creating links to the global economy; therefore, rebuilding tourism infrastructure throughout the deoccupied areas of Ukraine has become a top priority for Ukraine’s recovery after the war.
Keywords: infrastructure; tourism infrastructure